Meropenem Sensitivity Pattern of Bacterial Isolates Causing Neonatal Sepsis in Special Care Neonatal Unit of Chattogram Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: Neonatal sepsis is recognized as an important public health problem with a high morbidity and mortality, mostly occurring in developing countries. Treatment of neonatal sepsis has become a challenge with the emergence of carbapenemase producing bacteria. The study was done to evaluate the sensitivity pattern of bacterial isolates against meropenem causing neonatal sepsis. Materials and methods: A total of 100 clinically suspected neonatal sepsis cases was enrolled in the study. Bacteriological profile and meropenem sensitivity pattern was done. Results: Among the 100 suspected neonatal sepsis cases, 28% were culture positive and 72% were culture negative. Klebsiella species was the predominant isolated bacteria. Searching meropenem sensitivity pattern, 42.31% bacterial isolates were found to be sensitive and 57.69% were resistant to meropenem. Klebsiella spp. showed 40.00% sensitive to meropenem, whereas Acinetobacter spp. 25.00%, E. coli 66.67%, Staph. aureus 50.00% & Pseudomonas spp. 50.00% sensitive. Conclusion: Meropenem is the drug of choice for serious infections but bacterial resistance against it is increasing day by day.JCMCTA 2019 ; 30 (1) : 43-46